2022
DOI: 10.3897/jhr.93.94621
|View full text |Cite
|
Sign up to set email alerts
|

Meteorus lucianae sp. nov. (Hymenoptera, Braconidae), a new parasitoid of the bud borer Crocidosema aporema (Lepidoptera, Tortricidae)

Abstract: Crocidosema aporema is a Neotropical Tortricidae moth that feeds on several wild and cultivated Fabaceae, and has a potential to cause economic damages. A new parasitoid wasp belonging to the genus Meteorus (Hymenoptera, Braconidae), which has been reared from C. aporema feeding on soybean in Brazil, is described and illustrated. A checklist of parasitoids previously recorded for C. aporema is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Crocidosema aporema is characterized as a major soybean pest in Argentina (Iannone & Parisi, 1979; Koch & Waterhouse, 2000) and Brazil (Almeida & Penteado‐Dias, 2022; Corrêa & Smith, 1976; PPQ, 2019). However, the results for both growing seasons in the present study clearly indicated that C. aporema had low potential to injure indeterminate Bt ‐trait soybean despite field infestations of more than 55%, substantially above the current ET of 30% (Panizzi, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crocidosema aporema is characterized as a major soybean pest in Argentina (Iannone & Parisi, 1979; Koch & Waterhouse, 2000) and Brazil (Almeida & Penteado‐Dias, 2022; Corrêa & Smith, 1976; PPQ, 2019). However, the results for both growing seasons in the present study clearly indicated that C. aporema had low potential to injure indeterminate Bt ‐trait soybean despite field infestations of more than 55%, substantially above the current ET of 30% (Panizzi, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The high tolerance of soybean to C. aporema injury observed in our study may be related to the fact that all C. aporema injuries in our trials occurred after the pod‐set (R 3 ) stage. Nevertheless, it is still important to point out that insecticides should be used with caution (Almeida & Penteado‐Dias, 2022), mainly when insect outbreaks occur during flowering.…”
Section: Discussionmentioning
confidence: 99%